10β-Hydroxyestra-1, 4-diene-3, 17-dione as potential antiproliferative agent: in vitro biological evaluation and in silico studies. Issue 24 (17th December 2022) - Canário, Catarina; Matias, Mariana; Brito, Vanessa de; Cruz-Vicente, Pedro; Soeiro, Pedro; Santos, Adriana O.; Falcão, Amílcar; Silvestre, Samuel; Alves, Gilberto
Abstract: 10β-Hydroxyestra-1, 4-diene-3, 17-dione (HEDD) is a natural product described as having neuroprotective activity. However, the cytotoxic properties of this quinol are barely studied. Thus, the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide assay was performed in six cell lines (MCF-7, T47-D, LNCaP, HepaRG, Caco-2 and NHDF). Additionally, an in vitro estrogenicity assay and a cell viability analysis together with in silico molecular docking studies were carried out in order to understand the potential mechanism of cytotoxicity. Computational predictions of its pharmacokinetic and toxicity properties were also performed. Surprisingly, HEDD displayed marked cytotoxic activity, particularly against hormone-dependent cancer cells and the flow cytometry analysis revealed that HEDD markedly reduced the viability of hepatic cancer cells. Molecular docking studies suggested a high affinity towards the estrogen receptor α and 17β-hydroxysteroid dehydrogenase type 1. Moreover, it was predicted that HEDD may have good oral bioavailability and a low maximum tolerated dose in humans. Graphical Abstract: UF0001